Successful Treatment of Delayed Localized Necrotizing Inflammatory Myositis After Severe Acute Respiratory Syndrome Coronavirus 2 mRNA-1273 Vaccine: A Case Report. (27th September 2022) - Li, Jennifer Chen; Siglin, Jonathan; Marshall, Michael S; Stemmer-Rachamimov, Anat; Bloom, Seth M; Blumenthal, Kimberly G
Abstract: Reported adverse reactions to the mRNA-1273 vaccine (Spikevax, Moderna Inc) against severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) range from mild, local delayed cutaneous reactions to rarer, more serious reactions such as myocarditis. Here, we describe the presentation and successful treatment of delayed, localized necrotizing inflammatory myositis following a third dose of the mRNA-1273 SARS-CoV-2 vaccine. To our knowledge, this is the first report of biopsy-confirmed, delayed inflammatory myositis after administration of an mRNA-1273 SARS-CoV-2 vaccine booster.